2022
DOI: 10.1177/07067437221144629
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Offending as a Function of Acquired Brain Injury Among Men in a High Secure Forensic Psychiatric Hospital

Abstract: Background Acquired brain injury (ABI) is a serious problem that disproportionately affects individuals in correctional services, but relatively little is known about ABI risks and correlates in forensic psychiatric services. Methods We conducted a retrospective chart review of all admissions to a high secure forensic hospital in Ontario, Canada from January 2009 to December 2012 ( n = 637) and collected data on ABI, psychiatric diagnoses, developmental disadvantage, criminal offending, and in-hospital aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…We would argue that this implies that the behavioural problems that were a reason for admission, and that may be related to the neurocognitive disorder, are not likely to be mislabelled as psychotic behaviours in patients that are known to have a neurocognitive disorder. This lower prevalence also corroborates with the finding of Belfry et al, 23 who reported lower prevalence of schizophrenia in forensic patients with acquired brain injury. The question remains, however, how these behavioural problems are interpreted in patients with an undiagnosed neurocognitive disorder.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We would argue that this implies that the behavioural problems that were a reason for admission, and that may be related to the neurocognitive disorder, are not likely to be mislabelled as psychotic behaviours in patients that are known to have a neurocognitive disorder. This lower prevalence also corroborates with the finding of Belfry et al, 23 who reported lower prevalence of schizophrenia in forensic patients with acquired brain injury. The question remains, however, how these behavioural problems are interpreted in patients with an undiagnosed neurocognitive disorder.…”
Section: Discussionsupporting
confidence: 91%
“…In summary, although at face value our study suggests that only 3.0% of prisoners in a PPC have a neurocognitive disorder, we hypothesise that the true prevalence of neurocognitive disorders in this population is higher, based on findings in the literature 20,23 and the relatively high prevalence of unspecified neurocognitive disorder. We call for increased attention to neurocognitive disorders in forensic psychiatry, both in clinical practice, as well as in research, including more attention for cross-cultural neuropsychological assessment.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations